Knowledge and Attitude Regarding Human Monkeypox Virus Infection among Nurses: A Cross-Sectional Study - Moustaq Karim Khan Rony RN, BSN, MSS, MPH; Priyanka Das Sharmi RN, MSS; Dilruba Akter RN, BSN; Mst. Rina Parvin RN, BSN; Hasnat M. Alamgir PhD (SAGE Publishing, 2023)
Introduction Monkeypox (Mpox) is an infectious illness that can spread to humans through infected humans, animals, or contaminated objects. In 2022, the monkeypox virus spread to over 60 countries, raising significant public health concerns. Nurses play a vital role in patient care and have critical responsibilities in managing infected patients and being aware of the potential impact on the general population. Objective This study aimed to investigate the knowledge and attitudes (KAs) of Bangladeshi nurses regarding monkeypox infectious disease. Methods A cross-sectional study was conducted between October 2022 and March 2023 to evaluate the KA of nurses. Semi-structured and self-administered questionnaires were used, distributed via Google Form, and a convenient sampling technique was implemented. The dataset was analyzed using the Chi-square test, multivariable logistic regression, and Pearson correlation coefficient. Results A total of 1047 datasets were included in the final analysis. Overall, 57.97% of the participants demonstrated good knowledge, and 93.12% of the respondents had a positive attitude towards monkeypox disease. Female nurses exhibited better knowledge (adjusted odds ratio (AOR) 1.36; 95% confidence interval (CI) 0.88-1.98) and a more positive attitude (AOR 1.64; 95% CI 1.12-3.00) than male nurses. Furthermore, a strong correlation was observed between good knowledge of monkeypox disease and a positive attitude (r = 0.76, p  < 0.001), while poor knowledge moderately correlated with a negative attitude (r = 0.53, p  < 0.001). Conclusions Given the need for further improvement in KA, we recommend implementing additional training programs to enhance the abilities and motivation of nurses in effectively managing patients affected by monkeypox.